2020
DOI: 10.1111/hiv.12958
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between diabetes and depressive symptoms in men with or at risk of HIV infection

Abstract: The aim of the study was to compare the prevalence of comorbid diabetes and depressive symptoms in men living with HIV (MLWH) with that in men without HIV infection and to determine associations between glycaemic control and depressive symptoms. Methods Participants included 920 MLWH and 840 men without HIV infection from the Multicenter AIDS Cohort Study (MACS) with available data regarding glycaemic status [categorized as normal for fasting blood glucose (FBG) < 100 mg/dL, prediabetes for FBG 100-125 mg/dL, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 43 publications
(46 reference statements)
0
1
0
Order By: Relevance
“…Our results showed that the underlying disease is a risk factor for wound infection, which is consistent with the results of the above study. This is because diabetic patients have a decrease in protein and fat synthesis and an increase in catabolism, which reduces tissue self‐repair, regeneration and resistance to infection, and a high‐glucose environment that favours bacterial growth, which is not easy to remove, all of which can affect wound healing and lead to the development of wound infections 34,35 . Buchanan et al 36 also suggested that diabetes mellitus may be a risk factor for wound infection.…”
Section: Discussionmentioning
confidence: 99%
“…Our results showed that the underlying disease is a risk factor for wound infection, which is consistent with the results of the above study. This is because diabetic patients have a decrease in protein and fat synthesis and an increase in catabolism, which reduces tissue self‐repair, regeneration and resistance to infection, and a high‐glucose environment that favours bacterial growth, which is not easy to remove, all of which can affect wound healing and lead to the development of wound infections 34,35 . Buchanan et al 36 also suggested that diabetes mellitus may be a risk factor for wound infection.…”
Section: Discussionmentioning
confidence: 99%